The Next Step: The California Cybersecurity Institute’s Anti-Trafficking Virtual Reality Immersion Training - Borrelli, Danielle; Greer, Benjamin Thomas (Anti-Trafficking Review, 2021)
Digital gaming and virtual learning platforms have expanded the boundaries of experiential based anti-trafficking training. Virtual reality provides a technological mechanism for immersive storytelling through the simulation of a physical presence within an artefact using software and specialised hardware. The success of virtual-based immersive training is directly dependent on a series of factors, including realism, re-playability, and supplemental in-person training. This article describes the California Cybersecurity Institute’s anti-trafficking immersion training programme, which advances beyond awareness education to test law enforcement and first responder-specific skills and biases. This multi-layered programme looks to incorporate all concepts of ‘serious gaming’ within law enforcement and humanitarian communication.